Magnetic resonance enterography of Crohn's disease. (January 2014) - Naganuma, Makoto; Hisamatsu, Tadakazu; Kanai, Takanori; Ogata, Haruhiko
<x xml:space="preserve">Abstract</x> Magnetic resonance enterography (MRE) has been reported to be a useful modality for the evaluation of luminal inflammation and extraintestinal complications in Crohn's disease (CD). A recent study indicated that the diagnostic ability of MRE was comparable to the diagnostic ability of other devices, such as ileocolonoscopy. MRE can be performed repeatedly because there is no radiation exposure. Therefore, MRE is useful as a method of follow-up for younger patients with established CD. It is useful for evaluating the efficacy of medical treatments, such as biologics. MRE can detect small intestinal lesions even if the endoscope does not pass through the stenosis. The concerns of availability of expertise and the costs associated with MRE should be addressed so MRE can be widely used for CD patients in the near future.